A Major Advance in the Synthesis of Fluoroalkyl Pyrazoles: Tuneable Regioselectivity and Broad Substitution Patterns. Issue 32 (30th June 2016) - Schmitt, Etienne; Panossian, Armen; Vors, Jean‐Pierre; Funke, Christian; Lui, Norbert; Pazenok, Sergiy; Leroux, Frédéric R.
Abstract: A novel approach towards highly functionalized fluoroalkyl pyrazoles was developed by using fluoroalkyl amino reagents in combination with a variety of fluorinated ketimines. Tuneable introduction of fluoroalkyl groups in the 3‐ and 5‐positions was possible by using vinamidinium intermediates or the corresponding enamino ketones after hydrolysis. These high‐value building blocks can give rise to a large number of analogues for bioactivity screening and discovering new heterocyclic bioactive ingredients in various life science fields. Abstract : FAR better : An efficient method to access highly functionalized fluoroalkyl pyrazoles with tuneable regioselectivity is reported. The method uses fluoroalkyl amino reagents (FARs) in combination with a variety of fluorinated ketimines (see scheme).